The Implementation of Flash Games in Teaching Writing Descriptive Text to The Seventh Grade of SMP Muhammadiyah 10 Surabaya - Miftahul Huda; Gusti Nur Hafifah; Armeria Wijaya (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2016)
Writing is one of skill which is being basic skill in English learning. Writing is very important to be learned because it is being a compulsory in teaching English which the students have to be well mastered. There are many kinds of genres insert the teaching writing. One of them is writing descriptive. The teacher used flash game as media in teaching learning process in order to it could be motivated the students who lack motivations and minimize boredom faced. The purpose of the study was to know the implementation of teaching writing descriptive text by using flash game and the students’ responses toward teaching writing descriptive text using by using flash game to seventh grade of SMP Muhammadiyah 10 Surabaya. The researcher designs his research a descriptive qualitative research. The subject of this study is seventh grade of SMP Muhammadiyah 10 Surabaya. To collect the data in this study, the researcher used four points to collect the data. They were the observation checklist, field notes, interview the teacher, and questionnaire as the technique. The implementation of flash game in teaching writing descriptive text was very effective to teaching writing descriptive text because it could be motivated and helped the students during teaching learning process. Students were not only being motivated and helped but also being participated actively during teaching learning process in the class. The result of students’ questionnaire was very good because most of students like very much with the implementation of flash game in teaching writing descriptive text. The researcher classified the questions into four factors. They were the first factor was about the students’ opinion about the material, it consisted into four questions. The second factor was about the students’ opinion about the teacher’s role during teaching writing descriptive text by using flash game, it consisted into two questions. The third factor was about the students’ opinion about the flash game, it consisted into three questions. The fourth factor was about the students’ opinion about general evaluation, it consisted into one question. That was way, the implementation of flash game in teaching writing descriptive text to seventh grade of SMP Muhammadiyah 10 Surabaya was very successful because it can reach the aim of teaching writing descriptive text in the class and also it makes the students being participate actively during teaching learning process.